Women and men as sacrifice victims in Euripides’ tragedies. A gender perspective - Rubiera Cancelas, Carla (ARYS. Antigüedad: Religiones y Sociedades, 2020)
In Ancient times, sacrifices were characteristic in many different religions. Many elements were used to perform those practices, including the killing of human beings. Historiography studies whether these human sacrifices were real and examines specific evolution stages within those societies. However, the aim of this article is to analyze the victims. The study of human sacrifice reveals which characteristics were used to select those men and women, why they were chosen to be killed for their communities’ own good. From a gender perspective, I have focused my study in some of the cases which appear in Euripides’ Tragedies and analyzed them in relation to lineage and virginity.
Keywords: Human sacrifice; tragedies; gender; lineage; virginity; Greece